Cultural analysis of gastronomic practices represented in the new media - D. A. Bandurko, (Ukrainian Cultural Studies, 2022)
The article studies the problem of nutrition, which comes as the basis for the existence security of an individual as well as of any community. The transition to thermo-processed food was a necessary stage of humanization in the process of human genesis from nature, as long as the increase in its assimilation provides a time release for other activities and, accordingly, their more complex specialization. Therefore, the transformation of "raw into cooked" (C. Lévi-Strauss), which becomes a part of gastronomic practice basic definition, implies not only the technology of cooking (the actual operations with food), but also the process of human self-production, which has its social and even cosmological contexts. We should understand this process within historical dynamics. After all, each historical and cultural epoch makes a "food revolution" (F. Braudel) and creates its own "Tastes of Paradise" (W. Schivelbusch). The new field of food studies, which is actively developing on the basis of existing humanitarian scientific approaches to media and gastronomic practices taken together, presents actual material for cultural studies.Gastronomic practices engaging into the global media space, and gastronomic culture acting at the present stage as a process of de-differentiation of the structures of everyday life and the media environment, represent actual objects of cultural studies. This approach reveals such a basic unit of analysis as cultural practice, defined as a routine type of behavior consisting of interrelated elements (forms of culture of presence and culture of meaning, human activity, objects and ways of using them). Cultural practice in a gastronomic dimension is the process of cooking as an element of self-production of man and community, of the care for themselves and for others. The distinction between mediation as a process of cultural products communication as media production (in this case, people and things in the production and consumption of food in the unity of material, social and spiritual dimensions) and mediatization as a process of media hierarchy constructing (which becomes apparent at the level of media formation) is another important element of the gastronomic practices study in the situation of new media.
Keywords: cultural analysis; gastronomic practices; food culture; new media; cultural practices; mediatization